Pengaruh pelatihan public speaking terhadap kepercayaan diri remaja Desa Harapan Jaya, Kec. Way Ratai Kab. Pesawaran Provinsi Lampung dalam kegiatan sosial - Azizah, Meylin (Universitas Al Azhar Indonesia, 2025)
Public speaking is among the vital skills of building adolescent self-confidence, specifically social engagement in the community. As stated in this research, the impact of public speaking training towards the self-confidence of adolescents in Harapan Jaya Village, Lampung District, Lampung City will be ascertained. The research method utilized is quantitative through the survey approach. The respondents of the research comprised adolescents who had joined a public speaking training course. The data were collected through a questionnaire that measured respondents' self-confidence perception after they had attended training. Analysis was conducted to monitor the relationship between training and fostering adolescent self-confidence in social activities. Findings revealed that public speaking training was able to build adolescent self-confidence, especially to be brave to speak in public, to express opinions confidently, and to join community activities. The findings of this study imply that public speaking training is a potential program in developing adolescent potential at the village level. Keywords: public speaking, self-confidence, adolescents, social activities, communication